Amorphous polymeric nitrogen – toward equation of state - Yakub, L. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
The thermodynamic properties of amorphous polymeric nytrogen are analyzed theoretically basing on free energy expansion. An approach allowing estimating Helmholtz free energy of high-pressure disordered condensed phases of nitrogen is proposed. The approach is based on expansion of the excess entropy on interatomic correlations and tested on existing Monte Carlo simulation data. Some specific problems arising on this way and their possible solutions are discussed.